Lawfare and Mediafare as Character Attacks: The Cases of Ada Colau, Mónica Oltra and Irene Montero in Spain - Sara García-Santamaría; Germán Llorca-Abad; Dolors Palau-Sampio (Profesional de la información, 2025)
Spanish politicians have endured numerous attacks on their reputation, led by conservative parties and extra-parliamentary actors linked to the far-right (Pozas, 2024; Urías, 2024). This article examines the media coverage of criminal lawsuits against progressive politicians in cases suspicious of lawfare. Lawfare and mediafare appear as two intertwining ways of character assassination. This is because lawfare is not unidirectional, but relational; it only works if the media echoes it (De-Pádua Andrade, 2018). Media coverage gives lawsuits the necessary “massiveness” for the character assassination to be effective (Bielsa; Peretti, 2019). Even if the targets are deemed innocent, the target’s reputation and that of their parties can be damaged forever, often destroying their political career. To account for the complex intertwining between lawfare and mediafare, we have conducted a content analysis of 354 news items from three quality newspapers that represent a wide ideological spectrum: eldiario.es (left-wing), elpaís.com (centrist) and elmundo.es (conservative) and added the ultraconservative okdiario.com (Guerrero-Solé, 2022; Palau-Sampio; López-García, n.d.; Pérez, 2021). The article examines three cases that legal experts have qualified as prototypical examples of lawfare (Martín-Pallín, 2023; Montaner, 2023; Urías, 2024). These are the cases of progressive female politicians Irene Montero, former Minister of Equality; Ada Colau, former Mayor of Barcelona, and Mónica Oltra, former vice-president of Valencia’s regional government. The analysis shows that mediafare operates through logos, ethos and pathos character attacks that question the politicians’ reputation, credibility and emotional stability, leading to media rather than legal judgements of guilt. By portraying all politicians as corrupt, lawfare and mediafare contribute to the normalization of corruption and discredit of democratic politics.